2010
DOI: 10.4049/jimmunol.1000490
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Regulation of Heat Shock Protein 90-Chaperoned Self-DNA and CpG-Oligodeoxynucleotide for Type I IFN Induction via Targeting to Static Early Endosome

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 45 publications
0
35
1
Order By: Relevance
“…However, a breakdown of innate tolerance to self-nucleic acids occurs when tissue injury or necrosis causes the release of some endogenous molecules, including antimicrobial peptides such as LL37 and nuclear protein high-mobility group box 1 protein, which help to promote stabilization and delivery of associated innate ligands including nucleic acids into early endosomes. We have recently demonstrated that human extracellular Hsp90 complexed with CpG-A or self-DNA stimulates production of a large amount of IFN-α from pDCs via endosomal targeting [19]. In this study, we showed that extracellular Hsp90 found in SLE sera bound to self-DNA and is thus capable of stimulating IFN-α production when pulsed onto pDCs.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…However, a breakdown of innate tolerance to self-nucleic acids occurs when tissue injury or necrosis causes the release of some endogenous molecules, including antimicrobial peptides such as LL37 and nuclear protein high-mobility group box 1 protein, which help to promote stabilization and delivery of associated innate ligands including nucleic acids into early endosomes. We have recently demonstrated that human extracellular Hsp90 complexed with CpG-A or self-DNA stimulates production of a large amount of IFN-α from pDCs via endosomal targeting [19]. In this study, we showed that extracellular Hsp90 found in SLE sera bound to self-DNA and is thus capable of stimulating IFN-α production when pulsed onto pDCs.…”
Section: Discussionmentioning
confidence: 64%
“…Self-derived nucleic acids, however, may reach endolysosomes in an inflammatory or autoimmune situation, where a variety of nucleic acid-binding proteins such as autoantibodies, anti-microbial peptide LL-37 [17], and a nuclear protein, high-mobility group box 1 protein [18], are complexed with host nucleic acids. We have recently demonstrated that host DNA complexed with Hsp90 stimulated TLR9 signaling, leading to robust IFN-α production [19]. These complexes are resistant to degradation, reach the endolysosomes, and stimulate TLR7 and TLR9.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is mounting evidence that both subcellular localization and endosomal pH can influence the ability of endosomal TLRs to signal. For example, the TLR9 response to exogenous CpG DNA is dependent on specific endosomal localization and acidification (Guiducci et al , 2006; Yao et al , 2009; Okuya et al , 2010; Hazeki et al , 2013; Duhamel et al , 2016). Sasai et al (2010) showed TLR9 signaling leading to activation of type I IFN but not pro‐inflammatory cytokine genes require TLR9 trafficking from endosomes to a specialized lysosome‐related organelle dependent on AP‐3.…”
Section: Discussionmentioning
confidence: 99%